Diversity of epilithic diatoms from coral reef ecosystem of Bawean Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Luthfi OM, Risjani Y, Subramani N, Rybak M, Park J, B?k M, Witkowski A. 2024. Diversity of epilithic diatoms from coral reef ecosystem of Bawean Island, Indonesia. Biodiversitas 25: 4642-4663. This study investigates the diversity and community structure of epilithic diatoms in the coral reef ecosystems of Bawean Island, Indonesia. A total of 137 taxa from 49 genera were identified from coral rubble habitats across four distinct locations. The Shannon-Wiener Diversity Index (H') and Dominance Index (C) were used to assess species diversity and dominance, revealing that Station 4 exhibited the highest diversity (H' = 3.88) and lowest dominance (C = 0.03), while Station 2 had the lowest diversity (H' = 2.55) and highest dominance (C = 0.09). Evenness values (E = 0.9) were consistent across all sites, indicating a uniform distribution of species. The findings suggest that coral rubble provides unique microhabitats conducive to diatom diversity, challenging the conventional understanding that habitat diversity correlates positively with species diversity. The study also compares Bawean Island's diatom diversity with other regions, noting its intermediate diversity level, which may be influenced by its geographical position between Kalimantan and Java. The presence of dominant species like Diploneis crabro, Petroneis marina, Halamphora coffeiformis, and Trachyneis aspera underscores the ecological significance of these diatoms in coral reef ecosystems. This research fills a significant gap in our understanding of the marine biodiversity and ecological dynamics of Bawean Island, highlighting the importance of diatoms in maintaining the health and stability of coral reef ecosystems and its potential implications for future research and conservation efforts.
Keywords: Biodiversity, coral reef ecosystems, microhabitats, Shannon-Wiener Index, volcanic island